PENERAPAN INFORMATION COMMON DI PERPUSTAKAAN PERGURUAN TINGGI DI ERA NET GENERATION - Fransiska Timoria Samosir (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2016)
The development of information and communication technology has changed the behavior of higher education students in the era of net generation. Such students are recognized by their high dependency on gadgets to have their social activities. This condition demands academic libraries to change their appearances in order to improve their services that meet the needs of the net generations. Libraries will become a second home for their users. To achieve this, libraries can implement a concept called infor- mation common. Information common is a concept of library improvement that involves information technology. The concept, which includes learning, discussion, information technology, experiment, cy- bercafé, and information desk, expects optimum utilization of spaces and facilities to provide comfortable rooms for users.